The effects of training group exercise class instructors to adopt a motivationally adaptive communication style. (10th June 2016) - Ntoumanis, N.; Thøgersen‐Ntoumani, C.; Quested, E.; Hancox, J.
Abstract : Drawing from self‐determination theory (Deci & Ryan, 2002), we developed and tested an intervention to train fitness instructors to adopt a motivationally adaptive communication style when interacting with exercisers. This was a parallel group, two‐arm quasi‐experimental design. Participants in the intervention arm were 29 indoor cycling instructors ( n  = 10 for the control arm) and 246 class members ( n  = 75 for the control arm). The intervention consisted of face‐to‐face workshops, education/information video clips, group discussions and activities, brainstorming, individual planning, and practical tasks in the cycling studio. Instructors and exercisers responded to validated questionnaires about instructors' use of motivational strategies and other motivation‐related variables before the first workshop and at the end of the third and final workshop (4 months later). Time × arm interactions revealed no significant effects, possibly due to the large attrition of instructors and exercisers in the control arm. Within‐group analyses in the intervention arm showed that exercisers' perceptions of instructor motivationally adaptive strategies, psychological need satisfaction, and intentions to remain in the class increased over time. Similarly, instructors in the intervention arm reported being less controlling and experiencing more need satisfaction over time. These results offer initial promising evidence for the positive impact of the training.